Smart Electromechanical Systems Group Interaction - Gorodetskiy, Andrey E.; Tarasova, Irina L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the latest achievements in the theory and practice of SEMS Group interaction by scientists from the Russian Academy of Sciences. It also discusses the development of methods for the design and simulation of SEMS Group interaction based on the principles of safety, flexibility and adaptability in behavior and intelligence and parallelism in information processing, computation and control. Recently, the task has been to ensure the functioning of robots within the framework of collective collaboration, so that they function efficiently, reliably and safely in real time. The topics covered include, but are not limited to, the following: - the planning behavior of the SEMS group; - methods and principles of designing of automatic control systems; - mathematical and computer modeling group interaction; - safety, flexibility and adaptability of the SEMS Group; - information-measuring soft- and hardware. This book is intended for students, scientists and engineers specializing in the field of smart electromechanical systems and robotics.
Emerging issues of Robots to be used in Groups -- Situational Control a Group of Robots based on SEMS -- Evolutionary Algorithms of Stable-Effective Com promises search in Multi-Object Control Problems -- Logical Control a Group of Mobile Robots -- Analysis of Use of Platonic Solids in Swarm Robotic Systems with Parallel Structure based on SEMS -- Intellectualization of The Process of Designing Smart Electromechanical Systems -- Reduction of Logical-Probabilistic and Logical-Linguistic Constraints to Interval Constraints in the Synthesis of Optimal SEMS -- Nature-Inspired Algorithms for Global Optimization in Group Robotics Problems -- Distributed Solution of Problems in Multi Agent Robotic Systems -- Principles of Docking of Modular Mobile Robots based on SEMS in their Group Interaction -- The Control Complex Robotic System on Parallel Mechanism -- A Coordinated Stable-Effective Compromises based Methodology of Design and Control in Multi-Object Systems.
Keywords: Control engineering; Robotics; Automation; Computational intelligence; Mechatronics; Control, Robotics, Automation; Computational Intelligence; Mechatronics